Penerapan Metode Metode Multi Attribute Utillity (MAUT) dengan Pembobotan Rank Order Centroid (ROC) dalam Pendukung Keputusan Pemilihan Mahasiswa Berprestasi - Tampake, Damian; Malau, Morando; Iskandar, Agus (Journal of Information System Research (JOSH), 2024)
Outstanding students are one of the most important parts of a university or institute where outstanding students can help raise the quality level of a university, both public and private. The achievements that have been achieved can become a benchmark for an active student in a particular field, but the number of students who excel becomes a problem for lecturers and lecturers to choose the best. Therefore, a Decision Support System is needed by applying the MAUT method with ROC weighting so that it is expected to produce a systematic and accurate ranking that makes it easier for teachers or lecturers to choose students who are eligible to be outstanding students. Obtaining calculations on several data with predetermined criteria, resulted in an accurate ranking on behalf of Melati Intan as the first rank on alternative A6 resulting in the best preference value of 10.3719.